Privacy watchdogs nip at Europe - Groom, Stephen; Hofer, Felix (PROMO (Danbury, Conn.), 2003)
The EU has passed many provisions dedicated to protecting personal data (especially financial data, medical records, genetic information and anything about children), and these affect marketing and promotion, mostly by slowing online business development. National data protection commissioners (special, independent authorities in charge of domestic implementation of EU directives) are especially alert to such marketing techniques as e-mail ads, electronic (pop up) ads, cookies, banners, Java scripting and spyware. The DP commissioners coordinate on a trans-national level through the Data Protection Working Party (DPWP), and address businesses based in and outside of the EU. Their powers extend to foreign subjects using equipment located in EU territory, and they have begun to enforce protocols for data processing on the Internet, through audiovisual systems and in direct marketing. Currently, the DP commissioners can apply sanctions - generally fines, but violations of privacy rules can be ruled criminal offenses, punished with imprisonment up to three years. Java scripts are software applications sent by a Web site to a computer, which allow remote servers to run applications on a user's PC. They can also collect and process personal data stored in user's PC for "profiling" without a user's awareness. DPWP considers these an invisible and illegitimate form of data processing.